PEMODELAN MATEMATIS POLA TANAM DAN JADWAL TANAM DAERAH IRIGASI BARO UNTUK MEMAKSIMALKAN KEUNTUNGAN - Uli Zahrati; Azmeri Azmeri; Syamsidik Syamsidik (Prodi Magister Teknik Sipil Unsyiah, 2019)
Daerah Irigasi (D.I.) Baro has a total area of 11.950 ha which consists of Baro Kanan area of 8,920 Ha and Baro Kiri area of 3.030 Ha. Maximum cropping intensity indeks of D.I. Baro ranged between 183%-213%. This shows that D.I. Baro is unable to meet the water needs for his extensive irrigation services. One of the factors that influence the planning and regulation of irrigation water is cropping pattern. The aims of this research is to get the best cropping pattern, so that the distribution of irrigation water discharge available in D.I. Baro can be done optimally, knowing the need of irrigation water in D.I. Baro, knowing the maximum plantable area that irrigation can irrigate, and knowing the maximum profit that can be achieved by optimization. Compilation of mathematical models to get the maximum benefit that can be achieved by optimizing land area. The data collected in this study is secondary data. The method used is an optimization method using a linear program.